Simultaneous improvement and genetic dissection of drought and submergence tolerances in rice (Oryza sativa L.) by selective introgression - Zhang, Chaopu; Li, Min; Rey, Jessica Domingo; Feng, Ting; Lafitte, Renee; Zheng, Tianqing; Lv, Yamei; Wu, Fengcai; Fu, Binying; Xu, Jianlong; Zhang, Fan; Zeng, Wei; et al. (Frontiers Media, 2023)
**Introduction:** Drought and submergence are contrasting abiotic stresses that often occur in the same rice crop season and cause complete crop failure in many rain-fed lowland areas of Asia.